Lattice strain distribution resolved by X‐ray Bragg‐surface diffraction in an Si matrix distorted by embedded FeSi2 nanoparticles. (10th November 2013) - Lang, Rossano; de Menezes, Alan S.; dos Santos, Adenilson O.; Reboh, Shay; Meneses, Eliermes A.; Amaral, Livio; Cardoso, Lisandro P.
<x xml:space="preserve">Abstract</x> Out‐of‐plane and primarily in‐plane lattice strain distributions, along the two perpendicular crystallographic directions on the subsurface of a silicon layer with embedded FeSi2 nanoparticles, were analyzed and resolved as a function of the synchrotron X‐ray beam energy by using ω:ϕ mappings of the (<inline-graphic xlink:href="ark:/27927/pgg3x936bv6" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) and (111) Bragg‐surface diffraction peaks. The nanoparticles, synthesized by ion‐beam‐induced epitaxial crystallization of Fe+‐implanted Si(001), were observed to have different orientations and morphologies (sphere‐ and plate‐like nanoparticles) within the implanted/recrystallized region. The results show that the shape of the synthesized material singularly affects the surrounding Si lattice. The lattice strain distribution elucidated by the nonconventional X‐ray Bragg‐surface diffraction technique clearly exhibits an anisotropic effect, predominantly caused by plate‐shaped nanoparticles. This type of refined detection reflects a key application of the method, which could be used to allow discrimination of strains in distorted semiconductor substrate layers.